MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI BUDAYA (SENI RUPA) MELALUI MEDIA AUDIO VISUAL DI KELAS VII8 SMPN 25 PADANG - Agung Budiyanto Sam, Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this research is to improve the learning results of grade VII8 SMP 25 Padang on the subjects of art and culture (Art) using audio visual media. This type of research this is a class action research (PTK) by utilizing the audio visual media, the research was carried out in February up to March 2019 in class VII8 SMP 25 Padang total students 32 people. Class action research through two cycles of two-cycle results obtained average results of student learning, on cycle I and cycle II 70.15 obtained average results of learning tally showed 80.31 increase that occurs in learning as a result of the improvement of learning.Keywords: Audio Visual Media. The Results Of The Study